Factors Affecting the Development of Bovine Respiratory Disease: A Cross-Sectional Study in Beef Steers Shipped From France to Italy - Padalino, Barbara; Cirone, Francesco; Zappaterra, Martina; Tullio, Daniele; Ficco, Gigliola; Giustino, Antonio; Ndiana, Linda Amarachi; Pratelli, Annamaria (Frontiers in Veterinary Science, 2021)
Bovine respiratory disease (BRD) is a complex, multifactorial syndrome and one of the major welfare and economical concerns for the cattle industry. This one-year cross-sectional study was aimed at documenting the prevalence of BRD-related pathogens and clinical signs before and after a long journey, and at identifying possible predisposition factors. Male Limousine beef steers (n=169) traveling from France to Italy were health checked and sampled with Deep Nasopharyngeal Swabs (DNS) at loading (T0) and four days after arrival (T1). Real-time quantitative PCR was used to quantify the presence of bovine viral diarrhea virus (BVDV), bovine respiratory syncytial virus (BRSV), bovine alphaherpesvirus 1 (BoHV-1), bovine coronavirus (BCoV), bovine adenovirus (BAdV), bovine parainfluenza virus 3 (BPIV-3), Histophilus somni, Mannheimia haemolytica, Mycoplasma bovis and Pasteurella multocida. Weather conditions at departure and arrival were recorded and the travel conditions were taken from the travel documentation. At T0, even if no animals displayed clinical signs, some of them were already positive for one or more pathogens. At T1, the number of animals displaying clinical signs and positive for BCoV, BAdV, BRSV, H. somni, M. haemolytica, M. bovis and P. multocida increased dramatically (p < 0.001). Transport also significantly increased co-infection passing from 16.0% at T0 to 82.8% at T1 (p < 0.001). An extra stop during the journey seemed to favor BRSV, M. haemolytica, and P. multocida (p < 0.05). Weather conditions, in particular sudden climate changes from departure to arrival and daily temperature variance, were found to be predisposing factors for many of the pathogens. The farm of arrival also played a role for BRSV, BAdV and H. somni (p < 0.05). BCoV increased dramatically, but no associations were found confirming that it spreads easily during transport phases. Our findings increased our understanding of factors increasing the likelihood of BRD-related pathogens shedding and can be useful to minimize the incidence of BRD and to implement animal transport regulations.